Modernization routes and relations between political and administrative spheres in Switzerland - Giauque, David; Siggen, Michael; Resenterra, Fabien (2009)
On the basis of three case studies, the authors attempt to identify changes in relationships between politicians and senior civil servants. Reforms inspired by `New Public Management' (NPM) have been implemented with the aim of creating a clearer separation between strategic activities entrusted to politicians, and the operational or managerial tasks generally under the remit of senior civil servants. By analysing the reforms implemented in three Swiss cantons, the article tests the hypothesis of strategic contingency of political-administrative relations, in particular in new of the different modernization routes selected in each of the three cantons. Obtained using both quantitative and qualitative survey techniques, the empirical results allow us to cast strong doubt on the emergence of greater distance between politicians and the civil service. While our results indicate elements of strategic contingency, no empirical factor allows us to identify greater separation between political and administrative spheres as a result of the reforms. In contrast, politicians and senior civil servants still freely admit their very high level of interdependence in designing, deciding and implementing public policies. Other explanations must therefore be put forward to explain this lack of distinction in the results, in particular institutional aspects. - Reproduced.
Keywords: Politicians - Switzerland; Civil service-Switzerland; Administrative reform - Switzerland; Administrative reform